The Charters and General Laws of the Colony and Province of Massachusetts 133 (1814) - (:unkn) unknown (General Publisher, 1633)
Prohibited the possession, trade, sale, and repair of guns, ammunition, armor, and weapons generally for “any Indian” enforced by fine.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES